Borneo Local Food Restaurant / Kathy Kanam ... [et al.] - Kanam, Kathy; Rezwin, Faizes; Azwanah, Norain; Tamin, Noor Hazriezah; Nuradilah, Raipen (2015)
The Local Food Restaurant will establish in that provided special menu that may attract people such as tourist and also local people . This restaurant also creating a successful business whereby wholesome food and beverages that usually popular by each ethnics in Sabah were promote to make Sabah Borneo be known among customers, local people , or tourist.